The Concept of Philosophy of Al-Hikmah Al-Muta'aliyah Mulla Shadra - Anwar, Anwar (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2024)
During the conflict between transcendental philosophy (Hikmah al-Muta'aliyah) and the philosophy of illumination (hikmah isyroqi), a new branch of philosophy known as transcendental philosophy (hikmah al-masysya'i) developed in Persia. Mulla Sadra called Hikmah al-Muta'aliyah as part of the first and second philosophical essays that had been written earlier. In his monumental work four journeys to God namely; al-Hikmah al-Muta'aliyah fi al-Asfar al-'Aqliyah al-Arba'ah. Al-Hikmah Muta'aliyah al-Sadra is a synthesis of intellectual illumination (isyroqi) , rational punishment and proof ('aql, burhan or istidlal) and religion and revelation. Sadra agrees that perfect knowledge is rational knowledge, combined with spiritual experience that can be obtained by those who follow the text of the Qur'an and al-Hadith. The source of knowledge is the text of the Qur'an, al-Hadith and the sayings of the imams and scholars combined with the experience of intuition and punishment. In receiving knowledge, the most appropriate method is Kasf supported by reason and interpretation of religious texts. Hikmah al-Muta'aliyah is considered the most important for Islamic philosophy, Islam which provides the highest philosophy, which is supported by Bayani, 'Irfani and Burhani in its analysis.